A bibliometric review of the research progress and trends in nanolubricants for refrigeration systems - Galang Sandy, Prayogo; Rizalman, Mamat; Mohd Fairusham, Ghazali; Nugroho, Agus; Catrawedarma, I G. N. Bagus; Muriban, Jackly; Muhammad Zikri, Japri (Society of Automotive Engineers Turkey, 2025)
This paper presents the first comprehensive bibliometric review of nanolubricant research, with a focus on its application in refrigeration systems from 2003 to 2025. The study aims to identify emerging research areas, key institutions, and critical research gaps within this field. Utilizing the Scopus® Elsevier database, the review covers publications from January 1, 2003, to June 17, 2025. Bibliometric analysis tools such as VOSviewer and Biblioshiny were employed to visualize research networks and trends, ensuring the accuracy and reliability of the findings. The results show a significant upward trend in nanolubricant research, particularly from 2012 to 2024, highlighting the growing importance of nanolubricants in enhancing the efficiency of refrigeration systems. Dominant research areas include engineering, materials science, and physics, with a focus on improving tribological efficiency and thermal conductivity. Key contributors to the field include India, China, and Malaysia, driven by substantial governmental support. The study also identifies the significant role of nanolubricants and nanorefrigerants in enhancing the thermodynamic and mechanical efficiency of vapor compression systems. Future research will likely focus on hybrid nanolubricants, which offer improved thermal and fluid management properties. This review highlights the rapid growth and interdisciplinary nature of nanolubricant research, emphasizing its potential for improving energy efficiency and system performance in refrigeration and automotive systems.